A Golgi Lipid Signaling Pathway Controls Apical Golgi Distribution and Cell Polarity During Neurogenesis - Xie, Zhigang (Dev Cell, 2018)
Phosphatidylinositol (PtdIns) transfer proteins (PITPs) stimulate PtdIns-4-P synthesis and signaling in eukaryotic cells, but to what biological outcomes such signaling circuits are coupled remains unclear. Herein, we show that two highly related StART-like PITPs, PITPNA and PITPNB, act in a redundant fashion to support development of the embryonic mammalian neocortex. PITPNA/PITPNB do so by driving PtdIns-4-P-dependent recruitment of GOLPH3, and likely ceramide transfer protein (CERT), to Golgi membranes with GOLPH3 recruitment serving to promote MYO18A- and F-actin directed loading of the Golgi network to apical processes of NSCs. We propose the primary role for PITP/PtdIns-4-P/GOLPH3/CERT signaling in NSC Golgi is not in regulating bulk membrane trafficking, but in optimizing apically-directed membrane trafficking and/or apical membrane signaling during neurogenesis.